Urban Open Spaces Supporting Physical Activity and Promoting Citizen's Health: A Systematic Review - Shahrzad Parto; Mohammad saeid Izadi; Mehrdad Karimimoshaver; Rouhollah Zaboli (Iranian Association of Health Education and Health Promotion, 2019)
Background and Objective: Due to the limited individual approach to behavior change, health promotion researchers use community-based initiatives to understand the factors affecting physical activity and promote the health of citizens. Urban open spaces can facilitate participation in physical activity and the health of citizens. The aim of this study is to identify the indicators, attributes, and dimensions of health promotion of citizens. Methods: This study was conducted in the first half of 2017 using the Cochran systematic review protocol. In order to search for studies related to public open areas and mobility and health of citizens, a search strategy was used in scientific directories and Web of Science databases to search for Latin articles and to use the SID for Persian studies. Through applying Meta synthesis, the extracted indices were classified in terms of the attributes and dimensions of the environment protecting the citizens' health. Results: The result of this research showed that 65 papers were eligible for analysis. After Meta synthesis studies, 62 indicators, 11 attributes and 4 main dimensions related to health protection and health promotion areas were identified. They include: physical, semantic, functional, and social individual. Conclusion: Urban open spaces can be a safe environment for citizens' health promotion activities. There should be aesthetics and green urban environments so that the citizens could safely and tranquilly carry out health promotion activities. These environments should be functionally and accessibly attractive and they should be a channel for citizens' socialization.